2006
DOI: 10.1007/s00429-006-0085-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of cerebrospinal fluid absorption sites in the pig and rat: connections between the subarachnoid space and lymphatic vessels in the olfactory turbinates

Abstract: The textbook view that cerebrospinal fluid (CSF) absorption occurs mainly through the arachnoid granulations and villi is being challenged by quantitative and qualitative studies that support a major role for the lymphatic circulation in CSF transport. There are many potential sites at which lymphatics may gain access to CSF but the primary pathway involves the movement of CSF through the cribriform plate foramina in association with the olfactory nerves. Lymphatics encircle the nerve trunks on the extracrania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 39 publications
1
50
0
1
Order By: Relevance
“…Experimental results (Di Chiro, 1964;Orešković et al, 1991;Sato et al, 1972;Sato et al, 1971;Sato and Bering, 1967) also show that CSF is formed outside the brain ventricles (in subarachnoid space). The results also show that CSF absorption occurs not only through villi arachnoidales, but also inside the brain ventricles (Brightman, 1968;Bulat et al, 2008;Cserr, 1971;Dodge and Fishman, 1970;Foley, 1921;Hassin, 1924;Orešković et al, 1991;Wright, 1972), along the nerve roots (Kido et al, 1976), from the subarachnoid space into the lymphatic system (Bradbury, 1981;Brierly and Field, 1948;Dandy, 1929;Johnston et al, 2005;Johnston et al, 2004;Koh et al, 2005;Koh et al, 2006;Weed, 1914), and high intraspinal absorption (Edsbagge et al, 2004).…”
Section: The New Working Hypothesis Of Cerebrospinal Fluid Hydrodynamicsmentioning
confidence: 87%
See 1 more Smart Citation
“…Experimental results (Di Chiro, 1964;Orešković et al, 1991;Sato et al, 1972;Sato et al, 1971;Sato and Bering, 1967) also show that CSF is formed outside the brain ventricles (in subarachnoid space). The results also show that CSF absorption occurs not only through villi arachnoidales, but also inside the brain ventricles (Brightman, 1968;Bulat et al, 2008;Cserr, 1971;Dodge and Fishman, 1970;Foley, 1921;Hassin, 1924;Orešković et al, 1991;Wright, 1972), along the nerve roots (Kido et al, 1976), from the subarachnoid space into the lymphatic system (Bradbury, 1981;Brierly and Field, 1948;Dandy, 1929;Johnston et al, 2005;Johnston et al, 2004;Koh et al, 2005;Koh et al, 2006;Weed, 1914), and high intraspinal absorption (Edsbagge et al, 2004).…”
Section: The New Working Hypothesis Of Cerebrospinal Fluid Hydrodynamicsmentioning
confidence: 87%
“…Since Shabo and Maxwell (1968) showed that the observed tubular system was probably a consequence of tissue histological preparation, and that the endothelium of arachnoid villi was, in fact, intact (Shabo and Maxwell, 1968), Tripathi and Tripathi (1974) proposed that there are temporary transmesothelial channels which allow the passage of CSF in bulk flow from the subarachnoid space to the venous blood Tripathi and Tripathi, 1974). In addition, there is a large amount of literature which suggests that the significant absorption of CSF (Va) occurs from the subarachnoid space to the lymphatic system (Bradbury, 1981;Brierly and Field, 1948;Dandy, 1929;Johnston et al, 2005;Johnston et al, 2004;Koh et al, 2005;Koh et al, 2006;Weed, 1914). Also, in spite of some other proposed places of CSF absorption (choroid plexuses, brain tissue, etc; see later), in physiological conditions the dural sinuses are still the main place of CSF absorption.…”
Section: Introductionmentioning
confidence: 99%
“…beyond the basal cisterns and CMJ. [21][22][23] Those CSF absorption devices declined possibly due to lengthy intracranial hypertension, especially in the patient with CSF diversion. 17,20,24 In other words, the previous ETV-treated OHCP might already coexist with "communicating HCP" due to the decrease in CSF absorption even before initial ETV.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a large amount of literature which suggests that a significant amount of the absorption of CSF occurs from the subarachnoid space to the lymphatic system (Bradbury, 1981;Brierly and Field, 1948;Dandy, 1929;Johnston et al, 2005;Johnston et al, 2004;Koh et al, 2005;Koh et al, 2006;Weed, 1914). Also, despite some other proposed places (choroid plexuses, brain tissue, etc; see later), in physiological conditions the dural sinuses are still the main place of CSF absorption.…”
Section: Cerebrospinal Fluid Absorptionmentioning
confidence: 99%
“…Additionally, it is believed that the choroid plexuses are also the place of CSF absorption (Dodge and Fishman, 1970;Foley, 1921). Furthermore, there is a large amount of literature which suggests that significant CSF absorption occurs from the SAS to the lymphatic system (Bradbury, 1981;Brierly and Field, 1948;Dandy, 1929;Johnston et al, 2005;Koh et al, 2005;Koh et al, 2006;Weed, 1914). It was also described that CSF has an extrachoroidal origin (Hassin, 1924), and that it is formed, except in the ventricles, within the subarachnoid space (Sato and Bering, 1967;Sato et al, 1971;Sato et al, 1972).…”
Section: Classical Hypothesis and Controversial Experimental Datamentioning
confidence: 99%